The longitudinal study of the effect of human capital on organisational innovation in Australian SMEs / Yasmin Kamall Khan and Laila Mohammad Kamaruddin - Kamall Khan, Yasmin; Mohammad Kamaruddin, Laila (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2016)
For the past two decades, organizational innovation has been studied by a number of scholars. This study has examined 1,423 SMEs, of various industries, in Australia from 2009-2011 by using Business Longitudinal Database (BLD) from the Australian Bureau of Statistics (ABS). Our research finding shows that human capital (HC) has a positive and significant effect on product and process innovation after the two-year interval. Since resource-based view RBV recommended that inimitable and valuable skills would mature over time, the impact of HC on organisational innovation is clear in this longitudinal study, supporting the perspective that managers ought to stress HC for better organisational innovation. HC affects effectiveness and efficiency only if employees fully utilise their capacities and aptitudes completely for the firm's objectives as long as they remain with the firm. Thus, managers should make every effort to maintain a long-tenured workforce in order to maintain the tacit and explicit knowledge in employees.